2010
DOI: 10.1523/jneurosci.1404-10.2010
|View full text |Cite
|
Sign up to set email alerts
|

Deep Brain Stimulation of the Center Median-Parafascicular Complex of the Thalamus Has Efficient Anti-Parkinsonian Action Associated with Widespread Cellular Responses in the Basal Ganglia Network in a Rat Model of Parkinson's Disease

Abstract: The thalamic centromedian-parafascicular (CM/Pf) complex, mainly represented by Pf in rodents, is proposed as an interesting target for the neurosurgical treatment of movement disorders, including Parkinson's disease. In this study, we examined the functional impact of subchronic high-frequency stimulation (HFS) of Pf in the 6-hydroxydopamine-lesioned hemiparkinsonian rat model. Pf-HFS had significant anti-akinetic action, evidenced by alleviation of limb use asymmetry (cylinder test). Whereas this anti-akinet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 36 publications
3
35
1
Order By: Relevance
“…Given the reported increase in firing of thalamic CM/Pf neurons in PD models (Jouve et al, 2010; Magnin et al, 2000; Orieux et al, 2000; Parr-Brownlie et al, 2009; Yan et al, 2008), and the decrease in thalamic connectivity with dMSNs after chronic dopamine depletion, we hypothesized that thalamostriatal inputs might be actively contributing to decreased spontaneous motor activity in parkinsonian mice through selective drive of the indirect pathway, relative to the direct pathway. We reasoned that disconnection of this pathway could rescue motor behavior.…”
Section: Resultsmentioning
confidence: 99%
“…Given the reported increase in firing of thalamic CM/Pf neurons in PD models (Jouve et al, 2010; Magnin et al, 2000; Orieux et al, 2000; Parr-Brownlie et al, 2009; Yan et al, 2008), and the decrease in thalamic connectivity with dMSNs after chronic dopamine depletion, we hypothesized that thalamostriatal inputs might be actively contributing to decreased spontaneous motor activity in parkinsonian mice through selective drive of the indirect pathway, relative to the direct pathway. We reasoned that disconnection of this pathway could rescue motor behavior.…”
Section: Resultsmentioning
confidence: 99%
“…It is generally adviced to inject desipramine or pargyline prior to 6-OHDA administration to protect noradrenergic neurons (Breese and Traylor, 1971) but this practice has been questioned (Debeir et al, 2005). There is a nonlinear dose dependent effect of 6-OHDA on noradrenergic neurons, and more recent work has shown that desipramine is not needed at the lower doses of 6-OHDA used in current study (Jouve et al, 2010). Notice that even in case of minor noradrenergic degeneration following 6-OHDA injection, the animal model would be closer to human PD where same degeneration of catecholaminergic cells is likely to be associated to the pathological state (Delaville et al, 2011;Mavridis et al, 1991;Pillon et al, 1989).…”
Section: -Hydroxydopamine Lesion Of the Sncmentioning
confidence: 88%
“…The injected solution contained 12 μl 6-OHDA hydrobromide (Sigma, Paris, France) dissolved in 6 μl of 0.9% NaCl with 0.1% ascorbic acid (Jouve et al, 2010). It is generally adviced to inject desipramine or pargyline prior to 6-OHDA administration to protect noradrenergic neurons (Breese and Traylor, 1971) but this practice has been questioned (Debeir et al, 2005).…”
Section: -Hydroxydopamine Lesion Of the Sncmentioning
confidence: 99%
“…However, the mechanism of action, specific target sites and stimulation parameters of this surgical approach must be further characterized. Recent studies indicate widespread basal ganglia cellular responses associated with efficient anti-parkinsonian effects of Pf DBS in rat models of PD (Goff et al, 2009;Jouve et al, 2010). Another DBS target that has recently generated some interest is the pedunculopontine nucleus (PPN), a conglomerate of cholinergic, glutamatergic and GABAergic neurons in the upper brainstem, tightly linked with the basal ganglia, thalamus and lower tegmental regions (MenaSegovia et al, 2004).…”
Section: New Targets For Dbs In Pdmentioning
confidence: 99%